In situ targeted MRI detection of Helicobacter pylori with stable magnetic graphitic nanocapsules - Yunjie Li (Nature Portfolio, 2017)
The effective detection ofHelicobacter pylori has been a challenge clinically. Here, the authors demonstrate the potential of magnetic nanoparticles for non-invasive diagnosis of H. pylori using magnetic resonance imaging in vivo.